2015
DOI: 10.1016/j.jalz.2015.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Prudent diet may attenuate the adverse effects of Western diet on cognitive decline

Abstract: High adherence to prudent diet may diminish the adverse effects of high adherence to Western diet on cognitive decline.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
106
6
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(120 citation statements)
references
References 57 publications
5
106
6
1
Order By: Relevance
“…In the Seasonal Variation of Blood Cholesterol Study [23], higher DII scores derived from both 24-hour dietary and 7-day dietary recalls also were associated with higher levels of hs-CRP. Finally, the DII includes saturated and trans fats, components of the Western diet with inflammatory potential, which have been associated with poor cognitive function in other studies [63,64]. …”
Section: Discussionmentioning
confidence: 99%
“…In the Seasonal Variation of Blood Cholesterol Study [23], higher DII scores derived from both 24-hour dietary and 7-day dietary recalls also were associated with higher levels of hs-CRP. Finally, the DII includes saturated and trans fats, components of the Western diet with inflammatory potential, which have been associated with poor cognitive function in other studies [63,64]. …”
Section: Discussionmentioning
confidence: 99%
“…4 Logistic regression models were adjusted for the following: age (years); ethnicity (white: yes or no); education (registered nurse, bachelor, or graduate); marriage status (married, widowed, or separated/divorced); menopausal status (pre-or postmenopausal; never, past, or current menopausal hormone use); smoking status (never smoked; pack-years: 1.0-9. between height and a prudent dietary pattern high in fruit and vegetables. Diet is one of the most important modifiable determinants of the "healthy aging phenotype" (10,11), and compelling evidence has suggested that a dietary pattern rich in fruit, vegetables, fish, whole grains, and starchy low-fat staple foods are likely to play key roles in promoting healthy aging (11,39,40). In addition to being genetically determined, attained adult height is a marker of early-life exposures affecting childhood and adolescent growth (e.g., maternal diet during pregnancy, childhood diet, infection, and psychological stress) (4, 41), which are thought to affect health during adulthood.…”
Section: Discussionmentioning
confidence: 99%
“…Our predicted proportions of macronutrients possibly lowering the chance of AD development, may be also used to divide the subjects of the previously published studies (for example described in [15,37,38]) to new trial groups according to macronutrient consumption and to reanalyze the statistical data to give new insights into the effectiveness of those particular diet changes in prevention of AD.…”
Section: Discussionmentioning
confidence: 99%